Strategi Pembelajaran Crossword Puzzle Untuk Meningkatkan Minat Belajar Peserta Didik - Siringoringo, Santi (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This research is motivated to improve the quality of human resources, as stated in the objectives of national education in the SISDIKNAS Law No. 20 of 2003. To achieve these national education goals, the government and educators have done many ways, one of which is to improve the quality of education by giving birth to a generation that is superior and achieves in all fields so that educational goals can be achieved optimally and learning outcomes are achieved well. One learning strategy that invites student interest and participation is the Crossword Puzzle learning strategy. The Crossword Puzzle strategy is one of the strategies for reviewing. From the results of class action research conducted in class IX-2 SMP Negeri 1 Onanrunggu, it can be concluded that students' interest in learning can increase through the application of the Crossword Puzzle learning strategy. this is in accordance with the increase in the percentage of students' interest in learning. In the pre-survey, the percentage of high categories was 0.00%, while in cycle I it increased to 7.40% and in cycle II it increased to 85.18%. And it can be concluded that the Crossword Puzzle learning strategy can increase students' interest.Keywords: crossword puzzle, learning interest, studentsAbstak: Penelitian ini dilatarbelakangi untuk meningkatkan kualitas sumber daya manusia, sebagaimana telah tercantum di dalam tujuan pendidikan nasional dalam UU SISDIKNAS No. 20 Tahun 2003. Untuk mencapai tujuan pendidikan nasional tersebut pemerintah dan para pendidik sudah banyak melakukan berbagai cara, salah satunya ialah meningkatkan mutu pendidikan dengan melahirkan generasi yang unggul dan berprestasi dalam segala bidang supaya tujuan pendidikan dapat tercapai secara optimal dan hasil belajar tercapai dengan baik. Salah satu strategi pembelajaran yang mengundang minat dan partisipasi siswa adalah strategi pembelajaran Crossword Puzzle. Strategi Crossword Puzzle adalah salah satu strategi untuk menijau ulang. Dari hasil penelitian tindakan kelas yang dilaksanakan pada kelas IX-2 SMP Negeri 1 Onanrunggu, bahwasanya dapat disimpulkan minat belajar peserta didik dapat meningkat melalui penerapan strategi pembelajaran Crossword Puzzle. hal ini sesuai dengan kenaikan persentase minat belajar peserta didik. Pada pra survey persentase kategori tinggi 0,00% sedangkan pada siklus I mengalami peningkatan menjadi 7,40% dan pada siklus II mengalami peningkatan menjadi 85,18%. Dan dapat disimpulkan bahwa strategi pembelajaran Crossword Puzzle dapat meningkatkan minat peserta didik.Kata kunci: crossword puzzle, minat belajar, peserta didik